Effectiveness of Plasmapheresis and IVIG in the Treatment of Guillain-Barre Syndrome: A Cross-Sectional Observational Study - Md Hasibuddin Khan,; Md Khairul Islam,; Sonia Rahman,; AKM Ferdous Rahman,; Subroto Kumar Sarker,; Mohammad Mohsin,; Mohammad Salim,; Sardar Mohammad Tanvir,; Md Habibullah,; Md Mozaffer Hossain, (Bangladesh Critical Care Journal, 2023)
Background: Plasma exchange and intravenous immunoglobulin (IVIG) are the most effective treatments for Guillain-Barre syndrome; both can improve patients' symptoms. However, limited clinical research is available in Bangladesh to compare the effectiveness of both treatment modalities. Aims: This study aimed to compare the effectiveness of plasmapheresis and IVIG in the treatment of Guillain Barre Syndrome. Method: It is a prospective analytical study carried out in the ICU at the Department of Anesthesia, Analgesia, Palliative & Intensive Care Medicine, Dhaka Medical College Hospital, Dhaka, and Transfusion Medicine Department, NINS. Study subjects were patients with GBS, irrespective of gender, race, ethnic group, and age. For this study, they were divided into Group A (treated by IVIG) and Group B (treated by plasmapheresis). The clinical outcome & disability grade were evaluated and compared between groups. Result: In this study plasmapheresis was associated with more improvement compared to IVIg, moreover there was a significant difference in the disability scores between the two groups after 12 weeks of treatment. Group B with plasmapheresis had a significantly lower mean disability score (1.26 ± 0.06) compared to Group A with IVIg (3.05 ± 0.17) with a p-value of 0.011 At presentation and immediate post-therapy, there was no statistically significant difference between the two treatment groups in terms of MRC grade. However, at the later time points (6 and 12 weeks), Group B (plasmapheresis) was associated with a statistically significant improvement in MRC grade compared to Group A (IVIg). Specifically, at six weeks, the mean MRC grade was 3.18 for Group A and 4.04 for Group B (p=0.038), and at 12 weeks, the mean MRC grade was 3.52 for Group A and 4.87 for Group B (p=0.019). The mechanical ventilation rate was higher in IVIg (51.4% vs 14.2%, respectively) group. The difference was statistically significant (p=0.017). The proportion of individuals with complete recovery was significantly higher in Group B (60%) compared to Group A (22.8%) with an odds ratio of 5.06 (95% CI: 1.79-14.31) and a risk ratio of 1.959 (95% CI: 1.24-3.01). The proportion of individuals with residual deficit was significantly lower in plasmapheresis (25.71%) compared to Group A (57.1%) with an odds ratio of 3.85 (95% CI: 1.40-10.59) and a risk ratio of 2.22 (95% CI: 1.18-4.18), and this was statistically significant. There was no statistically significant difference in the proportion of individuals who died between the two groups, with a p-value of 0.530. Conclusions: In point of comparison, plasmapheresis has a potential benefit over intravenous immunoglobulin. Bangladesh Crit Care J September 2023; 11 (2): 95-102